A prospective study, to determine adverse effects of anti-retroviral agents in rural tertiary care teaching hospital - Jaykare, Swapnil Chudaman; Patil, Jyoti Ramchandra; Motghare, Vijay Motiram; Padwal, Sudhir Laxmanrao; Deshmukh, Vinod Shivajirao; Pise, Harshal Nutanrao (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Acquired immunodeficiency syndrome (AIDS) is a disease of the human immune system caused by the human immunodeficiency virus (HIV). Objective of this study was to evaluate the adverse drug reaction profile of anti-retroviral drugs in HIV patients in terms of causality, severity and preventability. Methods: Patients newly started on ART were followed prospectively for a period of initial six months and were interviewed in person during their routine follow-up or visit following development of any ADRs. ADRs were screened clinically and investigated accordingly for causality, severity and preventability. Results: Out of 59 cases, zidovudine+lamivudine+nevirapine (ZLN) was the most commonly used ART regimen. A total 122 ADRs involving various systems were observed in these patients; majority being related to gastrointestinal system (54.10%). Most of these ADRs were observed in the ZLN regimen followed by the stavudine+lamivudine+nevirapine (SLN) regimen. On causality assessment in ZLN regimen, 74.58% of ADRs were possible, while 25.42% were probable. Severity assessment showed that most of the ADR were mild whereas on preventability assessment it was observed that most of the ADRs were not-preventable. Conclusions: Antiretroviral drugs are not solely responsible for the ADRs due to these medications; various co-morbid and predisposing conditions share the responsibility. An efficient pharmacovigilance is imperative by means of improving ADR reporting and monitoring, in order to improve compliance and acceptability of ART.